Metode Penukar Ion Dalam Penyisihan Ammonia Air Lindi Tpa Muara fajar Dengan Variasi Waktu Kontak Dan Ukuran Tanah Lempung - Khodijah Khodijah; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
water into the garbage heap that comes from rain water, drainage channels, ground water, or other resources available around Muara Fajar landfill. Shelters Muara Fajar landfill leachate potential to generate waste that seeps into the ground and flows on the surface of the soil around the landfill. Leachate originating from shelters litter may result in increasing levels of environmental pollution in the vicinity of Muara Fajar landfill. Has done research methods ammonium ion exchangers in isolation Muara Fajar landfill leachate with contacts and measure the time variation of clay. This study aims to determine the parameters of pollutant removal efficiency of ammonia (NH3) by ion exchange method using clay and compares the characteristics of leachate treatment with quality raw KEPMENLH / 51/10/1995. This study uses clay size variations -5 + 10; -10 + 15; -15 + 20 mesh and 60 contact hours; 120; 180 minutes. The analysis shows that the leachate characteristics of NH3 concentration 38.69 mg / L indicating a high enough quality and more than raw (Minister of Environment Decree No. 51 of 1995). Having done the flow of leachate recovered pollutant concentrations decrease. Factors influence size variations of clay and contact time effect on the efficiency of reduction of concentration, the larger the mesh size (smaller diameter clay) then recovered the high efficiency of the concentration of pollutants. The results showed that the efficiency was high in clay size -15 + 20 mesh and 180-minute contact time gives the best removal efficiency of 91.12% NH3. While the efficiency of the lowest available in the size clay -5 + 10 mesh that is Ammonia of 17.13%. Cation exchange capacity of 105 earned meq / 100 g sample.Key Words: leachate, Ion exchange, clay land